The Strategy of Islamic Education Teachers in Shaping the ReligiousCharacter of Students - Wibakti, Aji Restu; Iswandi, Iswandi; Nasrodin, Nasrodin; Purnomo, Joko; Suprapto, Suprapto (STAI Miftahul Ula Nganjuk, 2024)
The objectives of this research are: (1) to examine the religious disposition of students at MA AZ-ZAIN Lengkong Nganjuk, and (2) to identify the strategies employed by Islamic education teachers in shaping the religious character of these students. This research adopts a qualitative approach, utilizing a descriptive qualitative method. Data collection was conducted through in-depth interviews, observations, and documentation. The research informants included Islamic education teachers, curriculum advisors, the school principal, and students. The validity of the information was verified through member checking, followed by triangulation techniques. The findings of the research indicate that: (1) The religious character of students at MA AZ-ZAIN Lengkong Nganjuk is generally underdeveloped, as religious practices such as obligatory prayers and Sunnah prayers are insufficiently observed, largely due to an unsupportive environment. Despite this, students are willing to seek improvement in their religious character and demonstrate honest behavior. (2) The strategies employed by Islamic education teachers to shape students' religious character include modeling and exemplification, guidance, direction, the formulation of practical theories, habituation, training, mentoring, and leadership.